The Readiness of Probation Officers of the Implementation of Restorative Justice in Malaysia - Mohammad, Taufik; Azman, Azlinda (Universiti Sains Malaysia, 2016)
Probation officers or pegawai akhlak working in Social Welfare Department of Malaysia are among the most significant authority figures in juvenile offender’s life going through a criminal process. This implies that their voice and opinion is an important part of assessment process when it comes to delivering intervention measures for the juvenile offenders. The Malaysian government has already called for the implementation of restorative justice within its juvenile justice and this means that obtaining the probation officers’ feedback on this would be pivotal which is this study’s aim. Twelve probation officers working in several states in Malaysia were interviewed by phone and asked with their readiness and perception on three main components of restorative justice which included a dialogue/meet-up between an offender and his or her victim, apology/forgiveness, and reparation of harm. The responses showed a trend of acceptance but with a degree of wariness when it comes to reparation of harm which was seen material by the respondents. In addition, the probation officers also emphasized on the feasibility of restorative justice programmes on only certain types of crime. These probation officers’ thoughts on restorative justice and the implication on the possible implementation will be discussed further.